Sedimentary architecture of gravity flow deposits in the liushagang formation of the paleogene, weixinan sag, beibu gulf basin, South China sea - Gao, Yufei; Kong, Xingxing; Wang, Haifeng; Wang, Xiabin; Yin, Yanshu; Chen, Mei (Frontiers in Earth Science, 2025)
Gravity flow deposits record a variety of sedimentary processes preserved within depositional systems. However, comprehensive studies on the evolution changes of gravity flow depositional architectures from fault-proximal sources to rift-distal areas remain limited. In particular, large-scale cases studies that systematically integrate different types of gravity flow deposits are still lacking. Using data from cores, well logs, and three-dimensional seismic reflection, this study focuses on the lithofacies evolution and associated sedimentary architectures of the upper of the upper sequence of the Third Member of the upper Liushagang Formation in the Weixinan Sag, Beibu Gulf Basin, South China Sea. The results indicate that: 1) Lithofacies in the study area can be classified into coarse-grained and fine-grained types. Coarse-grained lithofacies dominate the fault-proximal zone, where conglomerate and sandstone account for 79% of the deposits, whereas fine-grained lithofacies prevail in rift-distal areas, with mudstone comprising 53%. 2) Coarse-grained lithofacies are mainly massive, poorly sorted, and subangular to angular, commonly containing floating gravels. In contrast, fine-grained lithofacies exhibit decreased gravel content, increased sandy material, and well-developed bedding structures such as graded bedding, wavy bedding, convolute bedding, ripple lamination, and lenticular bedding. 3) Lithofacies characteristics and proportional analysis indicate that debris flow deposits dominate the source-proximal region, while turbidite deposits represent the main depositional environment. 4) Debris flows develop in a divergent fan-shaped geometry, whereas turbidity currents form tongue-shaped lobate bodies. 5) These lobes are laterally assembled and vertically stacked, with individual lobes extending 1.2 km–1.5 km in width. They form the widely distributed thin-bedded interbedded sandstone-mudstone deposits within the Weixinan Sag. Overall, the depositional evolution reflects a shift from topographically elevated, fault-proximal debris flows to lower-relief, rift-distal turbidity currents systems. The underlying paleotopography exerted strong control on the distribution of deposits. These findings provide important insights into sedimentary processes in gravity flow systems, especially the development of thin interbedded mudstone and sandstone units, and have significant implications for predicting sediment distribution and improving hydrocarbon exploration and production efficiency.